Phytochemistry, Toxicity, and Antimalaria Activity of Mangrove Plant from Muara Badak Beach, East Kalimantan, Indonesia - Usman, Usman; Masruhim, Muh. Amir; Rahmadani, Agung; Erwin, Erwin (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
This study aimed to determine the secondary metabolite content, toxicity, and antimalarial activity of methanol extracts of mangrove leaves Avicennia marina, Rhizophora mucronata, and Sonneratia caseolaris. Mangrove leaf extraction by maceration using methanol solvent, then qualitative phytochemical test (color test), toxicity test by BSLT method using Artemia salina, and antimalarial activity test using Plasmodium falciparum strain 3D7 with Giemsa staining microscopic method. The content of secondary metabolite compounds of methanol extracts of the three mangrove leaf species are alkaloids, flavonoids, saponins, phenolic compounds, steroids, triterpenoids and tannins. The toxicity of methanol extract of R. mucronata mangrove leaves against A. salina is included in the strong category. Meanwhile, the toxicity of S. caseolaris is included in the moderate category and A. marina is in the weak category. Mangrove species R. mucronata and S. caseolaris have good activity against P. falciparum 3D7 with IC50 values < 30 Î¼g/ml, while A. marina shows poor activity against P. falciparum 3D7 with IC50 values > 50 Î¼g/ml. Other tissue parts of these three mangrove species still need further exploration for their bioactivity against A. salina and P. falciparum 3D7.